Creating better internships by understanding mentor challenges: findings from a series of focus groups - Joel R. Schneider; Truls Aaby; Sanne Boessenkool; Emma Falkeid Eriksen; Kristin Holtermann; Iver Martens; Jonathan Soulé; Ariel Steele; Susanne Zazzera; Gro I. van der Meeren; Gaute Velle; Sehoya Cotner; et al. (International Journal of STEM Education)
Abstract Background Despite demands to make higher education more relevant beyond academia, and a growing body of work testifying to the benefits of work-relevance programs (e.g., work-placements, or internships) for both students and the companies that host them, there is limited information available for those aiming to optimize these programs. For example, few have explored the challenges and needs of internship supervisors. Here, we focus on the experiences of supervisors in biology and geology programs across three Norwegian institutions. Specifically, through a series of focus groups, we asked internship supervisors about their motivations for serving as student mentors, any challenges they had faced, and what higher-education institutions could do to better prepare them for hosting students at their workplaces. Results Key challenges faced by supervisors include the need to tailor placements to individual student needs and capabilities, navigating the constraints imposed by academic structures, and addressing communication gaps between students, institutions, and workplace supervisors. Internship supervisors suggest enhancing communication strategies to better define roles and expectations, increasing support and training for supervisors, and establishing clearer, more collaborative frameworks for setting learning objectives with students. Conclusions The supervisors’ suggestions aim to ensure that internships are mutually beneficial, supporting both students' educational outcomes and the workplace needs. By focusing on the supervisor's perspective, we provide valuable insights into one aspect of implementing effective and rewarding internships (i.e., supervisor preparation), thereby suggesting pathways for future improvements in these high-impact educational practices.